Finding the value in social business - Kane, Gerald C. (MIT, 2014)
A recent survey by Deloitte and MIT Sloan Management Review suggests that companies are starting to derive real value from social business (defined to include activities that use social media, social software and technology-based social networks to enable connections between people, information and assets). However, that business value is concentrated most strongly in companies that have reached a certain level of sophistication in relation to their social business initiatives. MIT Sloan Management Review and Deloitte have been exploring the impact of social media on business over the past three years through surveys, data analysis and interviews with executives and academics. The latest survey explored whether companies are deriving value from their social business initiatives. Sixty-two percent of managers surveyed report that their organization's social business initiatives are at least somewhat successful at meeting their stated business objectives, while 63% of respondents report that social business has positively affected business outcomes at their company. Fifty-nine percent of respondents in multinational companies report that social business helps them operate across geographies. Perhaps equally compelling is the extent to which individual employees indicate the value of social business to their daily work. Fifty-seven percent of respondents say that it is at least somewhat important for them to work for companies with mature social business practices, while 46% of respondents say that social business is at least somewhat important for decision making in their day-to-day role. A key factor in whether companies are able to derive positive benefits from social business is social business maturity. The researchers asked survey respondents to envision a company with ideal social business practices and then to assess how close their company was to that ideal. The higher a respondent rates his or her company, the more likely they are to report that the company is deriving business value from its social business initiatives. For example, 92% of respondents from the companies with the most mature social business practices say that social business helps them operate across geographies. The data shows that, based on maturity, different groups share distinctive social business practices. Thus, while incremental improvements to existing social business practices are likely to yield positive business outcomes, the kinds of benefits asso...
Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed April 27, 2015)
Keywords: Social media -- Marketing; Internet marketing; Marketing sur Internet